2010
DOI: 10.1002/adsc.201000035
|View full text |Cite
|
Sign up to set email alerts
|

Efficient Tandem Biocatalytic Process for the Kinetic Resolution of Aromatic β‐Amino Acids

Abstract: We describe a simple and efficient enzymatic tandem reaction for the preparation of enantiomerically pure b-phenylalanine and its analogues from the corresponding racemates. In this process, phenylalanine aminomutase (PAM) catalyzes the stereoselective isomerization of (R)-b-phenylalanines to (S)-a-phenylalanines, which are in situ transformed to cinnamic acids by phenylalanine ammonia lyase (PAL). Preparative scale conversions are done with a mutated PAM with enhanced catalytic activity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 29 publications
0
14
0
1
Order By: Relevance
“…Recently, a tandem biocatalytic process was described by using the mutase activity of PAM to convert ( R )‐β‐phenylalanine to ( S )‐α‐phenylalanine in combination with PAL to deaminate ( S )‐α‐phenylalanine to cinnamic acid, finally yielding enantiopure ( S )‐β‐phenylalanine 14. As we have found that the Arg92Ser mutation converts PAM into an ammonia lyase accepting ( R )‐β‐phenylalanine, the mutated enzyme was tested for application in the kinetic resolution of rac ‐β‐phenylalanine (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a tandem biocatalytic process was described by using the mutase activity of PAM to convert ( R )‐β‐phenylalanine to ( S )‐α‐phenylalanine in combination with PAL to deaminate ( S )‐α‐phenylalanine to cinnamic acid, finally yielding enantiopure ( S )‐β‐phenylalanine 14. As we have found that the Arg92Ser mutation converts PAM into an ammonia lyase accepting ( R )‐β‐phenylalanine, the mutated enzyme was tested for application in the kinetic resolution of rac ‐β‐phenylalanine (Figure 4).…”
Section: Resultsmentioning
confidence: 99%
“…Due to its PAL activity, PAM can be also applied to produce a mixture of (S)--and (R)--arylalanines (51). The combined use of PAM and PAL allows the preparation of (S)--arylalanines from their racemates (52). In this process, PAM isomerizes the (R)--arylalanine and PAL selectively degrades the forming (S)--amino acid.…”
Section: Introductionmentioning
confidence: 98%
“…The production of taxol by Taxus species ( T. chinensis , T. cuspidata , T. wallachiana , and T. canadensis ), andrimid by Pantoea agglomerans , and enedyine C‐1027 chromophore by Streptomyces globisporus indicated that an aromatic 2,3‐aminomutase in the producer organism was necessary to form the β‐amino acid related fragment in these secondary metabolites from the corresponding α‐amino acid. In addition to their role in nature, phenylalanine 2,3‐aminomutases (PAMs) gained increasing synthetic importance in the production of various unnatural β‐arylalanines . PAM catalysis starting from α‐amino acids or racemic β‐amino acids could be applied to produce various unnatural β‐amino acids through kinetic resolution or asymmetric ammonia addition to arylacrylates, even in cascades coupled with isomerization of racemic α‐amino acids in conjunction with a promiscuous racemase .…”
Section: Introductionmentioning
confidence: 99%